Swellable Ciprofloxacin-Loaded Nano-in-Micro Hydrogel Particles for Local Lung Drug Delivery - Du, Ju (AAPS PharmSciTech, 2014)
Incorporation of drug-loaded nanoparticles into swellable and respirable microparticles is a promising strategy to avoid rapid clearance from the lung and achieve sustained drug release. In this investigation, a copolymer of polyethylene glycol grafted onto phthaloyl chitosan (PEG-g-PHCs) was synthesized and then self-assembled with ciprofloxacin to form drug-loaded nanoparticles. The nanoparticles and free drug were encapsulated into respirable and swellable alginate micro hydrogel particles and assessed as a novel system for sustained pulmonary drug delivery. Particle size, morphology, dynamic swelling profile, and in vitro drug release were investigated. Results showed that drug-loaded nanoparticles with size of 218 nm were entrapped into 3.9-μm micro hydrogel particles. The dry nano-in-micro hydrogel particles exhibited a rapid initial swelling within 2 min and showed sustained drug release. Preliminary in vivo pharmacokinetic studies were performed with formulations delivered to rats by intratracheal insufflation. Ciprofloxacin concentrations in plasma and in lung tissue and lavage were measured up to 7 h. The swellable particles showed lower ciprofloxacin levels in plasma than the controlled group (a mixture of lactose with micronized ciprofloxacin), while swellable particles achieved higher concentrations in lung tissue and lavage, indicating the swellable particles could be used for controlling drug release and prolonging lung drug concentrations.